Analisis Faktor Yang Mempengaruhi Lama Mencari Kerja Dalam Perspektif Ekonomi Islam (Sudi DI Desa Reului Mangat Kecamatan Jangka Buya Kabupaten Pidie Jaya) - Z, Zahra; Fuad, Zaki; Dianah, Azimah (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2021)
This study aims to see how the influence of education, ability, and age on the length of looking for work in an Islamic economic perspective in Reului Mangat Village, Jangka Buya District, Pidie Jaya Regency. Technical analysis of the data in this study is multiple linear regression analysis using a questionnaire. The results of this study indicate that education, ability, and age simultaneously have a positive and significant effect on the length of time looking for work in the village of Reului Mangat. Partially, education and ability have a positive and significant effect on the length of ti me looking for work, while age does not partially have a significant effect on the length of time looking for work in Reului Mangat Village.